Associação entre concentrações de pyriproxyfen e spinosad com baixa ecotoxicidade como estratégia sustentável para programas de controle de Aedes aegypti - Santos, Vanessa Santana Vieira (2023)
Traditional interventions to control Aedes aegypti prioritize the intensive use of pesticides, leading to the selection of resistant mosquito populations, making vector control difficult and contributing to the increase in cases of arthropod-borne diseases. Additionally, these pesticide-based vector control actions have a significant environmental impact due to the lack of specificity for the target organism. Thus, developing efficient and ecologically correct strategies to combat the mosquito is crucial. In the first experimental study of this thesis, we performed toxicity tests using different concentrations of the biolarvicide spinosad to determine its effect on Aedes aegypti larvae and its environmental safety, using the non-target species Daphnia magna. The findings revealed that the use of the recommended concentration of spinosad in Aedes aegypti control programs showed high toxicity to Daphnia magna. We also identified that a 100 times lower concentration of the biolarvicide effectively controlled mosquito larvae and had a low impact on Daphnia magna reproduction. In the second experimental study, we investigated the effects of the association of low concentrations of spinosad and the pesticide pyriproxyfen on Aedes Aegypti larvae and evaluated ecotoxicological parameters in Daphnia magna. The results showed that this combination of larvicides was not toxic to microcrustaceans but acted synergistically to inhibit the development of adult Aedes aegypti mosquitoes, confirming our hypothesis. Importantly, these outcomes can subsidize Aedes aegypti vector-control strategies. In conclusion, the use of the association of low concentrations of spinosad and pyriproxyfen represents a more rational, effective, and sustainable solution for the needs of public health programs aimed at vector control.